A new solid-phase synthesis of oligoribonucleotides by the phosphoro-p-anisidate method using tetrahydrofuranyl protection of 2'-hydroxyl groups. - Iwai, S (1987)
Six nonaribonucleotides containing the 5'-splice site, one complementary nonamer and an octadecamer containing the 3'-splice site have been synthesized on a polymer support using the phosphoro-p-anisidate method. A 5'-linked 2'-O-tetrahydrofuranyl-N-protected nucleoside 3'-(o-chlorophenyl)phosphoro-p-anisidate was used as the starting nucleotide, and the chain elongated in the 3'-direction by removing the p-anisidate protecting group with isoamyl nitrite under neutral conditions. The octadecamer has been synthesized using dinucleotide blocks and a 3'-terminal trinucleotide.